Assessment of primers designed from the small ribosomal subunit rna for specific discrimination between babesia bigemina and babesia bovis by PCR - Linhares, Guido Fontgalland Coelho; Santana, Angela Patrícia; Laueman, Lloyd H.; Madruga, Cláudio R. (Ciência Animal Brasileira / Brazilian Animal Science, 2006)
Six pairs of species-specific primers were designed from the alignment of the sequences of the SS rRNA gene obtained from the Genbank database for Babesia bigemina (accession number X59604) and for B. bovis (accession number U06105). Three pairs of primers were designed specifically for B. bigemina and another 3 sets of primers for B. bovis. All oligonucleotide sequences selected as primers were examined for similarities to other organisms through the Genbank Blast procedure and these 6 sets of primers demonstrated high level of specificity. The synthetic oligonucleotides were also tested for specificity by PCR assay using genomic DNA extracted from 40 isolates of B. bigemina and 30 from B. bovis, obtained in six different States of Brazil. All 6 sets of primers were validated as 100% specific for the respective parasite. The PCR amplified the expected fragments for each set of primers, as follows: a) B. bigemina: primers GAU5 forward/GAU6 reverse with amplicon of 1,124 bp; primers GAU5 forward/GAU8 reverse with amplicon of 458 bp; primers GAU7 forward/GAU6 reverse with amplicon of 685 bp; b) B. bovis: primers GAU9 forward/GAU10 reverse with amplicon of 541 bp; primers GAU9 forward/GAU 13 reverse with amplicon of 883 bp; primers SOGIN forward/GAU 10 with amplicon of 1211 bp.KEYWORDS: Babesia bovis, Babesia bigemina, SS rRNA gene, PCR, primers, bovine babesiosis.